Polymer assisted enzyme induced carbonate precipitation for non ammonia emission soil stabilization - Yan, Z.; Gowthaman, S.; Nakashima, K.; Kawasaki, S. (Nature Publishing Group, 2022)
Biocementation using enzyme induced carbonate precipitation (EICP) process has become an innovative method for soil improvement. One of the major limitations in scaling-up of biocement treatment is the emission of gaseous ammonia during the urea hydrolysis, which is environmentally hazardous. In order to eliminate this shortcoming, this paper presents a series of experiments performed to evaluate a novel approach for preventing the ammonia byproducts in the EICP process via the use of polyacrylic acid (PAA). Through the adjustment of the pH to acidic, PAA not only promotes the enzyme activity, but also averts the conversion of ammonium to gaseous ammonia and its release, thus preventing any harm to the environment. The sand samples were treated with cementation solution and assessed for improvement in strength. Calcium carbonate content measurements and X-ray powder diffraction analysis identified the calcite crystals precipitated in the soil pores. Scanning electron microscopy analysis clearly showed that calcium carbonate was precipitated connecting soil particles, thus providing a uniaxial compressive strength (UCS) of up to 1.65 MPa. Overall, the inhibition in the speciation of gaseous ammonia shows the great potential of PAA for large-scale promotion of biocement.
Keywords: Enzyme induced carbonate precipitation; Bio-cement; Soil stabilization; Polyacrylic acid (PAA); Non-ammonia emission